Analysis of Work Environment, Training and Job Promotion on Employee Job Satisfaction of PT JNE Express Medan Main Branch - Wira Yudha Pratama; Wilchan Robain; Saimara AM Sebayang (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This research was conducted at PT JNE Express Main Branch Medan with the aim of analyzing the influence of the work environment, job training and job promotion on employee job satisfaction. The population is employees working in the company as many as 55 outbound employees with sampling with saturated samples so that the number of research samples is 55 respondents. The type of data used is primary data and the data source used is secondary data, data collection techniques using literature studies, surveys and observations. Data analysis techniques are multiple linear regression, classical assumption tests and hypothesis tests. The results of the study are that the work environment, job training and job promotion partially and simultaneously have a significant effect on employee job satisfaction in the company. There is a strong correlation between the work environment, job training and job promotion with employee job satisfaction in the company. Employee job satisfaction in the company can be explained by the work environment, job training and job promotion by 52.4% and the remaining 47.6%% can be explained by other variables not studied.